2019
DOI: 10.1002/prot.25833
|View full text |Cite
|
Sign up to set email alerts
|

All‐atom molecular dynamics simulations reveal how kinesin transits from one‐head‐bound to two‐heads‐bound state

Abstract: Kinesin dimer walks processively along a microtubule (MT) protofilament in a hand‐over‐hand manner, transiting alternately between one‐head‐bound (1HB) and two‐heads‐bound (2HB) states. In 1HB state, one head bound by adenosine diphosphate (ADP) is detached from MT and the other head is bound to MT. Here, using all‐atom molecular dynamics simulations we determined the position and orientation of the detached ADP‐head relative to the MT‐bound head in 1HB state. We showed that in 1HB state when the MT‐bound head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 74 publications
2
25
0
Order By: Relevance
“…In this study, we used all-atom explicit solvent simulations and coarse-gained SBM simulations, along with different freeenergy calculation methods, for a comprehensive understanding of the mechanisms governing propofol disruption. A large number of previous studies suggested the importance of order-disorder transition of NL for the forward movement of kinesin (31)(32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we used all-atom explicit solvent simulations and coarse-gained SBM simulations, along with different freeenergy calculation methods, for a comprehensive understanding of the mechanisms governing propofol disruption. A large number of previous studies suggested the importance of order-disorder transition of NL for the forward movement of kinesin (31)(32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that in this cycle, the two-head-bound E5 state (shown in a red circle in Fig. 1) is important for the processive movement of kinesin (32,33). In this state, the binding of ATP at the L head is inhibited to ensure that the two heads remain out of phase with each other rather than entering an ADP weak binding state with the MT.…”
Section: + + + + + + + + + + + + + + + + + + + + + _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ E E E E E E E E E E E E mentioning
confidence: 99%
“…For kinesin-1, it was assumed before that the MT-bound head with an open nucleotide-binding pocket (NBP) and an undocked NL (e.g., in ϕ and ADP states) has a high affinity for the other detached ADP-head while with a closed NBP and a docked NL (e.g., in ATP and ADP.Pi states) has a low affinity, 31,32 as prior all-atom molecular dynamics simulations showed. 33 It is proposed here that this assumption is also applicable to kinesin-13. The available structural data for kinesin-13 showed that when the head is bound to a tubulin in the middle region of MT in any nucleotide state its NBP is opened and its NL is undocked, while when the head in ATP state is bound to the curved tubulin at the MT end its NBP is closed and its NL is docked.…”
Section: Pathway Of Kinesin-13 Mcak Diffusing On Mtmentioning
confidence: 98%
“…The extra-turn formation and the β9 docking movement can pull the trailing head to the region near the next binding site on the microtubule. Interactions between the trailing head and microtubule or between the two heads [ 95 ] could pull the β10 to the plus end of the microtubule and facilitate the formation of the Asn latch. Consistent with this hypothesis, recent experimental results showed that the full neck linker docking process is completed upon ATP hydrolysis, not ATP binding [ 96 , 97 , 98 ].…”
Section: Docking Movement Of Kinesin-1 Neck Linker To Motor Domainmentioning
confidence: 99%
“…When the ATP hydrolysis and the Pi release complete, the trailing head gets into the ADP-bound state. In this state, the trailing head will bind with the microtubule weakly or detach from the microtubule [ 64 , 95 , 126 , 127 ] and the internal strain between the two motor domains disappears. With the release of the restriction from the internal strain, the neck linker of the leading head cannot maintain the backward orientation and, thus, the inhibition to ATP binding is relieved.…”
Section: Coupling Regulation Of Kinesin-1 Mechanochemical Cyclementioning
confidence: 99%